Pengaruh Intelijen Bisnis dan Strategi Bisnis Terhadap Pengambilan Keputusan - Tambunan, Paulus; Fauzi, Achmad; Syifa, Aisyah Nurul; Ratnasari, Ayu Eka; Ulfiona, Firsta; Sinaga, Ferori Rasna; Dandi, Fajar; Erlangga, Yoga Hafizh (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2024)
Business Intelligence encompasses a variety of strategies, processes, applications, data, technologies, and technical architectures implemented by companies to support the activities of data collection, analysis, and distribution of business information. Business Intelligence processes large amounts of information and data stored from various sources to make decisions. In making a business decision, a precise and accurate strategy is needed to avoid fatal errors that can harm the company. This research investigates the relationship between business intelligence and business strategy on decision-making using qualitative methods. By examining the relationship of theories and variables sourced from journals available online. The results of this literature review article are: 1) business intelligence affects decision making; 2) business strategy affects decision making.